Ghost boys - Rhodes, Jewell Parker (Little, Brown and Company, 2019)
Seventh-grader Jerome is mistakenly shot by a white police officer, and as a ghost, observes the turmoil in his community as a result of his death. He then meets the ghost of Emmett Till who helps Jerome understand how systemic racism led to his death, but also understand how far the effects of his death really go by introducing him to the grieving daughter of the police officer who struggles with her father's actions.